The Influence of E-Marketing Mix and Quality of Health Services on Patient Satisfaction at RSUD Prof. Dr. Soekarjo - Febrina, Dara Meutia Ayu; Pusparani, Kinanti Vionanda; Kusyanto, Fahmi Abdullah; Mubarok, Rizqi; Redjeki, Finny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The rapid development of information technology has brought about a fundamental transformation in the healthcare ecosystem, changing the paradigm of interaction between hospitals, medical personnel and patients. This research aims to explore the satisfaction felt by patients through existing health services at hospitals as well as explore the digital dimensions of health services, identify the most influential variables, and provide strategic recommendations for the development of hospital digital platforms. The data in this research was obtained through a questionnaire which was then analyzed using the Partial Least Squares (PLS) method with Structural Equation Modeling (SEM). The respondents in this study were patients at RSUD Prof. Dr. Soekarjo numbered 97 respondents. The research results show that the E-Marketing Mix variable which includes product, place, price, personalization, privacy, customer service, community and site elements has a significant influence on patient satisfaction at RSUD Prof. Dr. Soekarjo. Meanwhile, the dimensions of promotion, security and sales promotion do not have a significant effect on patient satisfaction at RSUD Prof. Dr. Soekarjo. The research results also show that service quality has a significant influence on patient satisfaction at RSUD Prof. Dr. Soekarjo. The results of this research indicate that the quality of hospital digital services does not just depend on technological aspects, but on the ability to create a personal, safe and meaningful experience for patients. Quality of service remains the main foundation in building satisfaction, where human aspects such as empathy, timeliness and professionalism of medical personnel are still very much taken into account..